Perlindungan Hukum Bagi Kreditur Pada Gugatan Actio Pauliana - Aida Nur Hasanah (Prodi Tata Negara (Siyasah) IAIN Langsa, 2022)
Legal protection is a legal remedy given to the rights of someone who is considered weak. Regarding the interests of the bankruptcy estate, the Court may request the cancellation of all legal actions of the debtor who have been declared bankrupt which harm the interests of the creditor, which was carried out before the bankruptcy declaration decision was pronounced. The cancellation can only be done if it can be proven that at the time the legal action was carried out, the debtor and the party with whom the legal action was carried out knew and should have known that the legal action would result in a loss to the creditor. Actio pauliana is present as a form of legal effort given by law to creditors to cancel the debtor's actions that harm the creditor. Actio Pauliana is regulated in Articles 42 to 50 of the Bankruptcy Law and PKPU.